Surgical Management for Acromioclavicular Joint Injuries - Dixita Tandel; Noel Samuel Macwan (Understanding Acromioclavicular Joint Injuries and its Management, Edition 1, 2024)
Background: Acromioclavicular (AC) joint injuries are more common in falls from two-wheelers in Asian countries and sporting activities in Western countries. There are numerous surgical techniques for treating separations of the AC joint reported. Surgical care can be divided into two main groups. In the first category, normal anatomy is restored through ligament reconstruction, whereas in the second, the joint is stabilized by modifying normal anatomy through osseous treatments. Acromioclavicular (AC) joint injuries can be surgically repaired using a variety of strategies, tactics, and procedures. Restoring the disturbed vertical and horizontal stability in an anatomically and biomechanically optimal manner is the main goal of treatment for these high-grade injuries. Conclusion: When treating dislocations of the Rockwood type I and II AC joints along with Type IIIA (horizontally stable), nonsurgical methods are typically advised. Furthermore, several studies advise surgeries for type III injuries in sportsmen and heavy manual labourers. When an AC joint suffers damage of the Rockwood type III B (horizontally unstable), IV, V, and VI injuries, a surgical procedure is typically advised.